A rare cause of dysmenorrhea-accessory cavitated uterine malformation: a case report - Subash Chandra Bose, Rajarajeswari Krishnasamy; V., Nandhana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Accessory cavitated uterine malformation is a newly recognized mullerian anomaly where the uterine cavity is normal unlike other Mullerian anomalies and hence needs to be described more accurately. These are non-communicating ULMs that occur contiguously along the wall of the uterus. This case report is about a 31 years old female who came with complaints of acute severe dysmenorrhea with a chronic course for the past 2 years and was evaluated for a similar episode in the past where she was diagnosed as fibroid with cystic degeneration and treated with SPRM and OCP which gave no relief from symptoms. With another exacerbation of symptoms two years later, patient was evaluated with an USG suggesting hemorrhagic degeneration in rudimentary horn and gave two differentials- fibroid with cystic degeneration and adenomyoma, wherein the latter was more likely. As a part of pre-op evaluation, MRI was done. Then came the third differential-ACUM [Accessory cavitated uterine mass]. Patient was counselled about the risk of infertility and uterine rupture in subsequent pregnancy as a post-op complication underwent laparoscopic surgery. Intraoperative and postoperative period was uneventful and HPE of the same confirmed the diagnosis. ACUM is a very treatable cause of severe dysmenorrhea and adequate awareness of this new entity will enable in making the diagnosis early.